Piala Dunia 2014: Cermin Keberhasilan Diplomasi Brazil Serta Dampaknya Bagi Perkembangan Ekonomi - Hartanto, Hartanto (Universitas Islam Negeri Raden Intan Lampung, 2016)
Diplomacy is an art in achieving the objectives of such country. Diplomacy fruitfulness is determined by various factors. This research aims to anatomize the diplomatic efforts of Brazil to host the FIFA 2014 World Cup as well as the factors that determine the successful of it achievement and impacts of the FIFA 2014 World Cup for the development of Brazil's economy. Research findings indicate that Brazil performs multilateral diplomacy conducted at FIFA. It is supported by the precise momentum, the good leadership of President Lula Da Silva in making Brazil as a leader in the Latin America, friendly foreign policy, and the support of the major powers. The positive impact of the FIFA 2014 World Cup in Brazil can be found in terms of political, economic and social benefits, while the negative impact appears in the form of increased crime rates.